PENGARUH USER EXPERIENCE DAN USER INTERFACE TERHADAP REPURCHASE INTENTION DENGAN E-SATISFACTION SEBAGAI VARIABEL INTERVENING PADA E-COMMERCE TOKOPEDIA - Rizal Muhammad; Sari Listyorini; Naili Farida (Universitas Diponegoro, 2025)
The development of technology has changed the way people live, including how they conduct transactions without meeting in person, which is now done through websites commonly known as e-commerce. This is supported by the high interest of the public in online shopping, which has led to the emergence of many e-commerce companies. To sustain their business and win the competition, companies must be able to encourage their customers to continue shopping on the same e-commerce platform. This study aims to determine the influence of user experience and user interface through e-satisfaction on repurchase intention among Tokopedia users in Semarang City. This research is classified as explanatory research, using non-probability sampling and purposive sampling as the sampling techniques. The sample used consists of 100 people who have made at least 3 purchases on Tokopedia. Data analysis was conducted using the Partial Least Squares (PLS) method with the help of SMART PLS software to test the validity and reliability of the constructs, as well as to analyze the influence of the variables studied. The results show a positive and significant effect of both variables, namely user experience and user interface, on e-satisfaction and repurchase intention. However, there is no direct effect between the user interface and repurchase intention.